1995
DOI: 10.1002/bbpc.199500118
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Programmed Surface Reaction Studies of the Methanol to Gasoline (MTG) Conversion over ZSM‐5

Abstract: The~ethanol to gasoline conversion over ZSM-5 has been studied by the Temperature Programmed Surface Reaction (TP~R) technique. The technique is able to delineate the two steps in the process: the dehydration of methanol to dimethyl ether and the subsequent conversion of dimethyl ether to hydrocarbons. The activation barr~ers associated with each step was evaluated from the TPSR profiles and are 108 kJ/mol and 195 kJ/mol respectively, The methanol desorption profile shows considerable change with the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Further, in the last case nearly no desorption of methanol is observed. Similar findings were reported by Jayamurthy et al 20 No experiment has shown any formation of aromatics. This is in accordance with the results of Ono et al 4 for small methanol concentrations.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Further, in the last case nearly no desorption of methanol is observed. Similar findings were reported by Jayamurthy et al 20 No experiment has shown any formation of aromatics. This is in accordance with the results of Ono et al 4 for small methanol concentrations.…”
Section: Resultssupporting
confidence: 91%
“…Haase and Sauer 15 compared their result with an experimental value of 110−120 kJ mol -1 , given only in a personal communication. This high value seems to agree with a heat of desorption of 120 kJ mol -1 determined for methanol desorption at higher temperarures . In contrast, a relatively low value of 62 kJ mol -1 , determined some years ago by Messow et al., is often used for comparison (see e.g., refs and ).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…1 There are sites in the two kinds of channel and at their intersections in H-ZSM-5, and the local electric field must be reflected in the states of the molecules adsorbed. 3 There have been extensive experimental studies on the state of MeOH using in situ IR analysis, [4][5][6][7] temperature programmed desorption, 8,9 and solid-state NMR analysis, 5,[10][11][12][13][14][15] as well as theoretical calculations. 1,[16][17][18] High-resolution solid-state 1 H NMR spectroscopy has recently shown that MeOH molecules form 'clusters' on the Brønsted acid sites of H-ZSM-5 at high coverages at ambient temperature.…”
mentioning
confidence: 99%